Merging Nitrogen Management and Renewable Energy Needs - Elizabeth Wilson; Pippa J. Chapman; Adrian McDonald (The Scientific World Journal)
The ARBRE (ARable Biomass Renewable Energy) project, the first large-scale wood-fueled electricity generating plant in the U.K., represents a significant development in realising British and European policy objectives on renewable energy. The plant is fueled by a mix of wood from short rotation coppice (SRC) and forest residues. Where feasible, composted/conditioned sewage sludge is applied to coppice sites to increase yields and improve soil structure. In the Yorkshire Water region, typical total N:P:K composition of composted/conditioned sludge is 2.9:3.8:0.3, respectively. Sludge application is calculated on the basis of total nitrogen (N) content to achieve 750 kg N ha-1, for 3 years’ requirement. Willow coppice forms a dense, widely spaced, root network, which, with its long growing season, makes it an effective user of nutrients. This, in combination with willow’s use as a nonfood, nonfodder crop, makes it an attractive route for the recycling of sewage sludge in the absence of sea disposal, banned under the EC Urban Waste Water Treatment Directive (UWWTD). Further work is required on the nutritional requirements of SRC in order to understand better the quantities of sludge that can be applied to SRC without having a detrimental impact on the environment. This paper suggests the source of N rerouting under the UWWTD and suggests the likely expansion of SRC as an alternative recycling pathway.